PODCAST WITH PEER ASSISTED LEARNING TO DEVELOP EFL LEARNERS LISTENING COMPREHENSION AND MOTIVATION - Shofiyatul Huriyah; Emilia Contessa (Universitas Putera Batam, 2020)
This study was aimed at investigating the effects of Podcast with Peer Assisted Learning in the EFL listening classroom. In conducting this research, pre-experimental design was used. The sample of this study was selected by using simple random sampling involving 27 students as the sample. The data collected were analyzed by using t-test (paired sample t-test) and percentage for two questionnaires, students’ motivation and perception. The result showed that (a) there was a significant difference in listening comprehension achievement before and after being taught by using Podcast with Peer Assisted Learning where t-obtained was 8.921 and the significance value was 0.000 which less than 0.05. On the basis of this result, it can be inferred that listening comprehension achievement of students before and after teaching by using podcast with peer-assisted learning was substantially improved. (b) The percentage score for learning motivation from the students was (55.6%) in high level, moderate 29.6% and low level was (5%). This score was considered students have high level of learning motivation. (c) most of the students gave positive perceptions on the use podcast with peer assisted learning in listening classroom. It can be concluded that teaching using podcast with peer assisted learning can develop the students listening comprehension achievement.